Amino equatorial effect of a six-membered ring amino acid on its peptide 310- and α-helices. Issue 16 (22nd April 2015) - Hirata, Takayuki; Ueda, Atsushi; Oba, Makoto; Doi, Mitsunobu; Demizu, Yosuke; Kurihara, Masaaki; Nagano, Masanobu; Suemune, Hiroshi; Tanaka, Masakazu
Abstract: Two diastereomeric six-membered ring α, α-disubstituted α-amino acids (1 R, 3 R )- and (1 S, 3 R )-1-amino-3-methylcyclohexanecarboxylic acids (Ac6 c 3M ); side-chain restricted leucine analogs, were stereoselectively synthesized from (3 R )-3-methylcyclohexanone by a Bucherer–Bergs or Strecker reaction. Two series of homo-chiral homopeptides Cbz-[(1R, 3 R )- and (1S, 3 R )-Ac6 c 3M ] n -OMe, up to hexapeptides ( n =6), were prepared, respectively, and the preferred conformations of cyclohexane rings of amino acid residues and the peptide-backbones were studied. In solution, these peptides formed helical structures, but the helical-screw control to one-handedness was not possible for the hexapeptide length. In the crystal state, all (1 R, 3 R )-Ac6 c 3M residues formed cyclohexane chair form conformations with a 3-methyl substituent at equatorial orientation and an amino group at the axial position, whereas all (1 S, 3 R )-Ac6 c 3M residues assumed cyclohexane chair forms with the 3-methyl and amino groups at equatorial orientations. The preferred peptide-backbone structure of (1 R, 3 R )-Ac6 c 3M hexapeptide had ( P ) and ( M ) 310 -helices, and that of (1 S, 3 R )-Ac6 c 3M hexapeptide had ( P ) and ( M ) α-helices in the crystal state. Graphical abstract: